Determinantes del Índice de Percepción de la economía - Magendzo, Igal (2005)
The movements of the Index of Perception of Economy (IPEC) can be associated to changes in macroeconomic variables such as domestic activity, prices or wages. This document examines the importance of these variables in explaining the fluctuations of this index. When making estimations using series to mixed frequency (i.e., with monthly and quarterly data), the variables that are found to determine the evolution of the IPEC are: the variation in the real wage index, the CPI of micros, the Imacec, and employment, as well as the annual variation of the number of vacancies and unemployment according to the INE. These variables are robust to changes of specification.